THE PEOPLE’S REPUBLIC OF CHINA IN THE AZOV-NORTH BLACK SEA SUBREGION: PRESENT STATE AND FUTURE PLANS - BABAYAN, David (CENTRAL ASIA AND THE CAUCASUS, 2012)
The Azov-North Black Sea Subregion is one of the planet’s strategically important areas; it is where the interests of different countries meet and intertwine. It is also tied by multiple threads not only to the Azov-Black Sea Region, but also to different regions of Russia and Ukraine. The People’s Republic of China (PRC) is pursuing an active policy in the above-mentioned regions. Furthermore, it is primarily interested in the Crimea, which virtually adjoins the Caucasus, the Rostov region, and Donbass (particularly the Lugansk and Donetsk regions); by establishing contacts with them, the PRC is strengthening its position in the Northeast Black Sea and Azov regions. This kind of policy is in keeping with China’s overall geopolitical strategy in the Black Sea basin; below we will look at some of its vectors.